A multicriterial mathematical model for creating vehicle routes to transport goods - Kleprlík, Jaroslav; Bečičková, Markéta; Brázdová, Markéta (Transport, 2011)
The article describes modelling a vehicle route to transport goods and discusses models for determining vehicle routes for a single depot and more vehicles. Above all, the paper defines a mathematical model for determining a vehicle route for more depots, more vehicles and more types of transport requirements.First Published Online: 07 Jul 2011